Facile synthesis of PEDOT@rGO nanocomposites for novel electrochemical sensor for the determination of 4-chlorophenol in a real water sample - Chellappa, Vasanthi (Elsevier, 2024)
A sensitive electrochemical sensor was developed for the detection of 4-chlorophenol (4-CP) using the nanocomposite based on poly (3,4-ethylenedioxythiophene) and reduced graphene oxide (PEDOT-rGO). The GC electrode modified with the proposed nanocomposite was characterized using X-ray diffraction, Raman spectroscopy, scanning electron microscopy, and electrochemical impedance spectroscopy. The Raman analysis confirmed the successful incorporation of PEDOT onto the reduced graphene oxide (rGO) surface. It is also observed in the SEM analysis that PEDOT nanoparticles were spread over the rGO sheet. The lower charge transfer resistance (R ct ) values for PEDOT-rGO/GCE compared to PEDOT/GCE in electrochemical impedance spectroscopy confirms the unique conducting properties of rGO and the higher surface area of PEDOT in the proposed composite on the GCE surface. The cyclic voltammetric and differential pulse voltammetric (DPV) results has indicated that the PEDOT-rGO-modified glassy carbon electrode is an excellent electrocatalyst for the detection of 4-CP compared to PEDOT and rGO. This counterpart exhibited a good linear relationship in the range of 5 - 250 mu M, with a detection limit of 12 nM in the DPV technique. This sensor was also employed for the determination of 4-CP in river water samples. The accuracy of the analytical electrochemical sensor for 4-CP was comparatively analyzed using the obtained UV - visible spectral data, indicating a detection limit of 21 nM. Hence, the electrochemical method was successfully employed to obtain a lower detection limit for 4-CP than that for electronic absorption spectral observations. All the observed results were consistent with our expectations and showed that this novel PEDOT-rGO/GCE has good repeatability and stability and without any impactable interference behavior.